2019
DOI: 10.1038/s41593-019-0384-5
|View full text |Cite|
|
Sign up to set email alerts
|

L3MBTL1 regulates ALS/FTD-associated proteotoxicity and quality control

Abstract: Misfolded protein toxicity and failure of protein quality control underlie neurodegenerative diseases including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Here, we identified Lethal(3)malignant brain tumor-like protein 1 (L3MBTL1) as a previously unknown regulator of protein quality control, the loss of which protected against the proteotoxicity of mutant SOD1 or C9orf72 dipeptide repeat proteins. L3MBTL1 acts by regulating p53-dependent quality control systems that degrade misfolde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…To date, our independent screens using mutant SOD1 C. elegans models have identified several suppressors of proteotoxicity, including UBE4B and LSD1 (18), L3MBTL1 (19), and USP7. Further studies have revealed a common theme shared by these regulators of proteotoxicity: They all modulate posttranslational modifications of transcription factors that control the expression of genes in protein quality control and thereby influence the degradation and clearance of misfolded proteins (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, our independent screens using mutant SOD1 C. elegans models have identified several suppressors of proteotoxicity, including UBE4B and LSD1 (18), L3MBTL1 (19), and USP7. Further studies have revealed a common theme shared by these regulators of proteotoxicity: They all modulate posttranslational modifications of transcription factors that control the expression of genes in protein quality control and thereby influence the degradation and clearance of misfolded proteins (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…To date, our independent screens using mutant SOD1 C. elegans models have identified several suppressors of proteotoxicity, including UBE4B and LSD1 (18), L3MBTL1 (19), and USP7. Further studies have revealed a common theme shared by these regulators of proteotoxicity: They all modulate posttranslational modifications of transcription factors that control the expression of genes in protein quality control and thereby influence the degradation and clearance of misfolded proteins (18,19). A signaling hub in this regulatory network appears to be the transcription factor p53 (18,19); interestingly, USP7 has wellestablished roles in deubiquitinating p53 and its E3 ligase Hdm2 (42), suggesting that USP7 is part of the protein quality-control network.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations